Penyusunan Laporan Keuangan Sebagai Dasar Perhitungan Pajak Bagi Umkm Lubuk Minturun - Indrayeni Indrayeni; Ratnawati Raflis; Enny Arita; Ingra Sovita; Khadijah Ath Thahirah (LPPM Universitas Dharma Andalas, 2023)
Micro, small and medium enterprises have an important role for a country's economic growth. However, MSMEs are still unable to keep financial records properly. With good records, MSMEs will be able to compile financial reports as a basis for calculating income tax. In order to help MSMEs in Lubuk Minturun in compiling financial reports and calculating taxes, the Unidha Accounting S1 lecturer team carried out PkM activities. The number of participants who took part in this activity were 20 participants who came from various business actors. It is known that 80% of participants have not recorded their business, so they cannot calculate their business tax. One of the obstacles faced by most MSMEs is the low level of education of MSME actors, limited entrepreneurial and management competencies. Through this community service activity, it is hoped that it can help MSME actors to gain understanding and knowledge in compiling financial reports in accordance with applicable accounting standards, so that MSME actors can calculate their income tax.